Production of Arbuscular Mycorrhizal Spores by Providing Nasa Liquid Organic Fertilizer (LOF) - Husna Husna; Faisal Danu Tuheteru; Asrianti Arif; Sijebir Sijebir; Albasri Albasri; Wiwin Rahmawati Nurdin; Parwito Parwito; Mariana Zainun (Journal of Tropical Mycorrhiza, 2023)
Arbuscular mycorrhizal fungi (AMF) are root symbionts that are in symbiosis with the majority of plants and are generally found in terrestrial ecosystems. The propagation of AMF is influenced by many factors, including fertilization. This study aims to determine the increase in arbuscular mycorrhizal spore production by administering Nasa LOF. The research was conducted at the Plastic House of the Indonesian Mycorrhizal Association, Southeast Sulawesi Branch and the Laboratory of the Forestry Department, Faculty of Forestry and Environmental Sciences, UHO in January - April 2023 using a factorial Completely Randomized Design (CRD) with two factors, namely the first factor, the type of AMF including Glomus coronatum and Glomus claroideum and the second factor is Nasa LOF control, 2.5 ml/1000 ml water, 5 ml/1000 ml water. The results showed that the combination treatment of Glomus claroideum and administration of 5 ml Nasa LOF increased the number of spores in the 3rd month and spores after drying. Nasa LOF 5 ml is relatively applied for the production of Glomus claroideum.